Effects of high and low volume of strength training on muscle strength, muscle volume and lipid profile in postmenopausal women - Correa, Cleiton Silva; Teixeira, Bruno Costa; Bittencourt, Aline; Lemos, Leandro; Marques, Nise Ribeiro [UNESP]; Radaelli, Regis; Kruger, Renata Lopes; Reischak-Oliveira, Alvaro; Pinto, Ronei Silveira (Elsevier B.V., 2014)
Changes in lipid profile are considered a risk factor for cardiovascular disease (CVD), especially in postmenopausal woman who have been associated with age-related loss of muscle mass. The beneficial role of aerobic exercise in the prevention of CVD has been well documented. However, the effect of strength training has not been established. The purpose of this study was to determine the changes of lipoprotein levels after 12 weeks of different volumes of strength training and its correlation with strength and muscle volume in postmenopausal women. The participants were randomized into three groups: low volume (LVST; n = 12, 1 set) and high volume of strength training (HVST; n = 11, 3 sets), or control group (n = 12). Training groups performed 12 weeks of supervised strength exercises, 15 maximum repetitions, five times a week, 20 minutes for LVST and 40 minutes for HVST for each training session. Measurements included body composition, strength and muscle volume, as well as blood analysis (glucose, total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein) pre- and post-training. The HVST and LVST improved the one-repetition maximum knee extension strength (p < 0.001), maximal dynamic strength (p < 0.001), and muscle volume (p = 0.048). Post-training triglyceride was lower in HVST when compared to LVST and the control group (p = 0.047). Even though they present the same neuromuscular and morphological adaptations in postmenopausal women, the HVST is more effective than LVST in improving the lipid profile of postmenopausal woman, and can be considered as an ideal program of intervention to reverse changes in lipid metabolism commonly found in this group. Copyright (C) 2014, The Society of Chinese Scholars on Exercise Physiology and Fitness. Published by Elsevier (Singapore) Pte Ltd. All rights reserved.
Keywords: Aging; Menopause; Muscle strength; Muscle thickness; Strength exercise; Triglycerides